Scenario analysis, decision trees and simulation for cost benefit analysis of the cargo screening process - Sherman, Galina; Siebers, Peer-Olaf; Aickelin, Uwe; Menachof, David (COPPE/UFRJ, 2010)
In this paper we present our ideas for conducting a cost benefit analysis by using three different methods: scenario analysis, decision trees and simulation. Then we introduce our case study and examine these methods in a real world situation. We show how these tools can be used and what the results are for each of them. Our aim is to conduct a comparison of these different probabilistic methods of estimating costs for port security risk assessment studies. Methodologically, we are trying to understand the limits of all the tools mentioned above by focusing on rare events.